2022
DOI: 10.1101/2022.04.27.489658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

StandardRat: A multi-center consensus protocol to enhance functional connectivity specificity in the rat brain

Abstract: Task-free functional connectivity in animal models provides an experimental framework to examine connectivity phenomena under controlled conditions and allows comparison with invasive or terminal procedures. To date, animal acquisitions are performed with varying protocols and analyses that hamper result comparison and integration. We introduce StandardRat, a consensus rat functional MRI acquisition protocol tested across 20 centers. To develop this protocol with optimized acquisition and processing parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Despite partial associations with acquisition parameters, the sources leading to analysis failures remained largely unclear. These findings were also recently reproduced in rats, incorporating datasets from 46 different sites and identifying expected connectivity in 40.8% of all scans (Grandjean et al, 2022). The authors found, however, that by standardizing key aspects of scan acquisition across 20 sites, this could be improved to 61.8%, highlighting the importance of improving standards for acquisition and data quality evaluation.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Despite partial associations with acquisition parameters, the sources leading to analysis failures remained largely unclear. These findings were also recently reproduced in rats, incorporating datasets from 46 different sites and identifying expected connectivity in 40.8% of all scans (Grandjean et al, 2022). The authors found, however, that by standardizing key aspects of scan acquisition across 20 sites, this could be improved to 61.8%, highlighting the importance of improving standards for acquisition and data quality evaluation.…”
Section: Introductionmentioning
confidence: 81%
“…Motivated by the current variability in results from network analysis between mouse fMRI sites (Grandjean et al, 2020(Grandjean et al, , 2022, we further develop new tools for data quality assessment and provide novel insights into the underlying sources of data quality failures leading to downstream issues with network analyses. These tools are building upon an extensive body of human fMRI literature on confounds and data quality metrics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations